(untitled) (Eurasian Scientific Herald, 2022)
The main condition for the implementation of cognitive development of preschool children is a mechanism for children to study. The form of learning information about the world around the surrounding world is determined by the young features of the child. The educator encourages children’s pre-school children through the help of cognitive tasks and will actively ignore the skills and systematize children’s knowledge. The process of performing cognitive tasks requires voluntary, intellectual movement, which leads to positive activities that completes the cognitive movement.